An Efficient Method for C8-Prenylation of Flavonols and Flavanones - Kawamura, Tomoyuki; Hayashi, Moemi; Mukai, Rie; Terao, Junji; Nemoto, Hisao (Synthesis, 2012)
Synthesis of C8-prenylated flavonols and flavanones via the palladium-catalyzed 7-O-1,1-dimethylprop-2-enylation, followed by Claisen rearrangement is described. Two regioselectivities (carbon–carbon bond formation at either the tail or head of the prenyl group and carbon–carbon bond formation at either C8 or C6) were efficiently improved when acetic anhydride was used as a solvent instead of N,N-dimethylformamide.
Keywords: flavonoid; Claisen rearrangement; prenylation; Kaiho’s method; flavonols; flavanones